Fluid-Solid Interfacial Properties and Drag-Reducing Characterization of the Flexible Conical Microstructured Film Inspired by the Streamlined Body Surface of the Pufferfish - Zhu, Dongpo (Langmuir : the ACS journal of surfaces and colloids, 2024)
Given the challenges in accurately replicating the surface of the pufferfish, this study employed three-dimensional (3D) printing to create a model based on inverse modeling. The morphology of the pufferfish exhibits a streamlined configuration, characterized by a gradual widening from the anterior oral region to the central ocular area, followed by a progressive narrowing from the midabdominal region toward the caudal extremity. The RNG k-ε turbulence simulation results demonstrate that the streamlined body surface of the pufferfish diminishes differential pressure resistance. This enhancement promotes laminar flow formation, delays fluid separation, minimizes turbulence-induced vortices, and reduces frictional resistance. Moreover, the pufferfish's supple and uneven outer epidermis was simplified into a flexible, nonsmooth planar film to conduct fluid-solid coupling simulations. These revealed that the pufferfish's unique skin can absorb turbulent energy and minimize momentum transfer between the fluid and the solid film, lowering the fluid resistance during swimming. In summary, The high-efficiency swimming capacity of pufferfish stems not only from their streamlined body surface but also significantly from the unique structural characteristics and mechanical properties of their flexible skin. This research provides critical theoretical underpinnings for the design of functional bionic surfaces aimed at drag reduction